The importance of laboratory medicine in the era of COVID-19 pandemic: a challenge for patients, pediatricians, obstetricians, and clinical pathologists - Mussap, Michele (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
The dramatic and rapid widespread of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection is causing millions of infected subjects and thousand of deaths worldwide. The current global goal is to mitigate or suppress the burden of COronaVIrus Disease 2019 (COVID-19) and to adopt effective targeted therapies. Laboratory tests include molecular diagnostics and viral antigens recognition for the identification of SARS-CoV-2 in human biological materials, serologic methods for detecting serum antibodies against SARS-CoV-2 and routine blood and urine tests. Many molecular tests, mainly based on real-time polymerase chain reaction (RT-PCR), have been developed after the publication of the SARS-CoV-2 full-length genome sequence; several factors may affect their accuracy, including inadequate sample collection, thermal inactivation, viral load, and cross-reactivity. In-vitro diagnostic (IVD) companies have developed serologic methods optimized on high throughput analytical platforms; however very few methods currently detect IgM and the accurate quantitative measurement of antibodies are not still ready. Sensitivity and specificity require robust validation; point of care (POC) lateral flow immunochromatographic assays are far to be highly sensitive and specific and data obtained by these methods should be evaluated with caution. The effectiveness of serologic tests depends on the appropriateness of test request too. Routine biochemical data in adults with COVID-19 reveal alterations of various tests, including lymphopenia, thrombocytopenia, hypoalbuminemia, and serum elevation of several biomarkers, including D-dimer, ferritin, C-reative protein (CRP), cytokines. Cardiac troponins and N-terminal pro-brain natriuretic peptide (NT-pro BNP) are predictors of adverse outcome and death. Vertical transmission of SARS-CoV-2 has been not yet demonstrated exhaustively. Regrettably, in pregnant women, newborns and children with COVID-19, very limited and confusing data hamper a definitive conclusion on the value of routine laboratory tests. Emerging opportunities arise from the introduction of microbiomics, metabolomics, and pharmacometabolomics for improving patient’s care and outcome.